An Exploratory Case Study Using Events as a Software Size Measure - Hacaloğlu, Tuna; Demirörs, Onur; Demirörs, Onur (Springer, 2023)
Software Size Measurement is a critical task in Software Development Life Cycle (SDLC). It is the primary input for effort estimation models and an important measure for project control and process improvement. There exist various size measurement methods whose successes have already been proven for traditional software architectures and application domains. Being one of them, functional size measurement (FSM) attracts specific attention due to its applicability at the early phases of SDLC. Although FSM methods were successful on the data-base centric, transaction oriented stand-alone applications, in contemporary software development projects, Agile methods are highly used, and a centralized database and a relational approach are not used as before while the requirements suffer from a lack of detail. Today's software is frequently service based, highly distributed, message-driven, scalable and has unprecedented levels of availability. In the new era, event-driven architectures are appearing as one of the emerging approaches where the 'event' concept largely replaces the 'data' concept. Considering the important place of events in contemporary architectures, we focused on approaching the software size measurement problem from the event-driven perspective. This situation guided us to explore how useful event as a size measure in comparison to data-movement based methods. The findings of our study indicates that events can be promising for measurement and should be investigated further in detail to be formalized for creating a measurement model thereby providing a replicable approach.
Keywords: Software size measurement; Event; Functional size measurement; Case study; Effort